Implementasi Prinsip Mubadalah Faqihuddin Abdul Kodir dalam Relasi Pasangan Suami Istri Beda Agama - Aliya Karima; Lina Kushidayati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2026)
This study aims to analyze the implementation of the mubadalah principle developed by Faqihuddin Abdul Kodir in the relationship of interfaith married couples in Tanjungkarang Village, Kudus Regency. This research employed a qualitative method with a sociological approach through observation, in-depth interviews, and documentation techniques. The subject of this study was Pak Gogo’s family, who experienced an interfaith household after the husband returned to Christianity following the marriage. The findings reveal that the mubadalah principle is reflected in family relations through mutual respect for religious beliefs, egalitarian communication, flexible role-sharing, and deliberative decision-making. Religious differences did not become a source of conflict within the family; instead, they created a space for the growth of tolerance, empathy, and family harmony. The implementation of the principles of mitsaqan ghalidzan, zawwaj, taradhin, mu’asyarah bil ma’ruf, and musyawarah was evident in the couple’s daily life. This study confirms that the mubadalah perspective can serve as an ethical approach in understanding interfaith family relations oriented toward mutuality, justice, and shared well-being without emphasizing normative judgments regarding the legality of interfaith marriage.